Home Industry Tempe Marketing Strategy in Improving Economic Welfare in Ngepean-Menampu Village, Gumukmas District, Reviewed From Syariah Marketing - Puput Aprilia; Mu’awanah Mu’awanah (International Journal of Economics and Management Research, 2025)
The tempe home industry is one of the micro businesses that has great potential in improving the economic welfare of the community. In this context, an effective marketing strategy is needed to optimize sales and expand market share. This research aims to identify and analyze marketing strategies that can be implemented by tempe home industry players. The methods used include surveys and interviews with business actors, as well as market analysis to understand consumer preferences. The research results show that the use of social media, collaboration with local communities, and the development of innovative products are the keys to attracting consumer interest. Apart from that, improving product quality and after-sales service also plays an important role in building customer loyalty. By implementing the right marketing strategy, the tempeh home industry can not only increase income, but also contribute to improving the overall economic welfare of society.